Tabebuia barbata (E. Mey.) Sandwith: aspectos morfo-anatômicos, fitocosmético e de conservação de uma Bignoniaceae no Baixo Rio Negro. - Noronha, Nelsília Matos de (2010)
Tabebuia barbata (Bignoniaceae), pau d’arco or capitari is a tree in Central Amazonia, distributed by the River Orinoco, Negro and Amazon. In RDS Tupé is commonly used for production of wood and some for medicinal purposes. It has medicinal importance by the presence of Lapachol, which is characteristic of the Tabebuia. The Lapachol is a naphthoquinone with antitumor and anti-inflammatory properties. Other species of the genus are suppliers of bark extracts for use in cosmetics in the Europen Commom Market and the U.S. Aiming to generate strategies for conservation and sustainability use were found required minimum amounts of raw material (leaves and bark) to obtain extracts. The extracts were used in the formulation of shampoos and soaps. Thus, it sought to add value to the final product, pointing to another way of using capitarizeiro. The research enable us to verify the cosmetic potential of T. barbata the handmade scale because the natural abundance of plant population, the seasonality of water level and species (deciduous, flowering, seed production) and market in the region facing the bioproducts conditions show is impossible exploration on a large scale. The possible production of soaps and shampoos for Communities of RDS Tupé has an average level of technology, which may have added value to the “Amazon natural ” products . Tests should be conducted by checking the likely properties of plant extracts of T.barbata (antifungal and plasticizer keratin), and cytotoxicity. The characterization morpho-anatomical, this work validates the originality of raw material (quality control) which will serve as a reference through dissemination on specialized scientific journal. Keywords: Tabebuia barbata. Bignoniaceae. Central Amazon. Lapachol. Plant extract. Cosmetic. Bioproduct. Handmade scale. Biotechnology.